A heuristic evaluation of a pharmacy surveillance information system - Reza Abbasi; Mehrdad Farzandipour; Habiballah Rahimi; Yang Gong; Ehsan Nabovati (BMC Medical Informatics and Decision Making)
Abstract Introduction The pharmacy surveillance information system (PSIS) is intended to manage the dispensing practice of under-controlled drugs and substances. We designed and developed a PSIS for the first time in a developing country. This study aimed to evaluate the usability of this system using a heuristic evaluation method before the pilot implementation in outpatient pharmacies. Materials and methods The study was conducted in 2022 during the development of a pharmacy surveillance information system. Five evaluators examined the system using Nielson’s heuristic evaluation method. The detected usability problems were categorized into 10 Nielson’s usability principles, and their severity was calculated. Results In total, 91 unique usability problems were identified. The most detected usability problems were minor (60%). The “consistency and standard” (31%), “aesthetic and minimalist design” (28%), and “match between system and the real world” (12%) were the most frequent problems. Also, the “flexibility and efficiency of use” (mean = 2.9), “error prevention” (2.85), and “user control and freedom” (2.8) were the most severe problems. Conclusion The study has identified the most common and severe usability issues of an information system. It is important for the system developers to address these issues as it can significantly improve users’ trust and satisfaction. Therefore, all the identified usability problems were resolved before the system was implemented.